Effectiveness of repositioning splints and stabilization splints in the treatment of symptomatic temporomandibular joint disk displacement with reduction - Phanomporn Vanichanon (Chulalongkorn University, 2006)
Thesis (M.Sc.)--Chulalongkorn University, 2003